English Negative Polarity Item Any Acquisition by Indonesian Speaking Learners of English - Dian Kurniawati (PAROLE: Journal of Linguistics and Education, 2021)
This study conducted an approximate replication of Marsden, Whong, & Gil's (2018) ‘What’s in the Textbook and What’s in the Mind: Polarity Item Any in Learner English’. Forty Indonesian speaking learners of English knowledge of English Negative Polarity Item any was investigated and the results were compared with the results of the original study (ibid.) including the additional study conducted by the same authors (Gil et al., 2017). The purpose of this study is to provide a replicated and extended study to the reliability of the original study by investigating different populations and comparing their performance with the performance of the population in the original study as well as by adding an additional language item some to be tested in a Truth Value Judgment Task (TVJT). This study focused on English NPI any and how Indonesian speaker learners of English acquire its properties when the properties were both taught and not taught. The results confirmed the original study with an additional finding that there was no correlation between the learners’ knowledge of any with their knowledge of some. Therefore, it is suggested that the existing instruction of the use of any should no longer be contrasted with some, but presented in a more meaningful context.